Perbandingan Kemampuan Berpikir Kritis Siswa Kelas VII Semester II SMP Muhammadiyah 4 Sambi Boyolali Tahun Ajaran 2015/2016 Menggunakan Model Pembelajaran Problem Solving Dan Discovery Learning - Maftuhah, Laily; , Dr. Siti Chalimah, M.Pd (2016)
This research aims at comparing critical thinking ability for second semester of seventh grade students in SMP Muhammadiyah 4 Sambi Boyolali in 2015/2016 academic year by using problem solving and discovery learning model. Class of this research is VII A class (problem solving) and VII C class (discovery learning). The type of this research is quantitative approach. The technique of sampling is by using simple random sampling. The statistical data analysis are using independent sample t test. The result of using in independent sample t test = 5% shows that there is differentiation. It based on the value of asymp sig. 0,036 > 0.05 so that there is significantly differentiation with problem solving and discovery learnig. Discovery learning class include in the medium category with 0,37. Problem solving class is in the low category with 0,17. Based on the result of data analysis, the conclusion is there is differentiation significant critical thinking ability in two models of learning that is learning by using discovery learning is better.